A Prognosis System for Periimplant Diseases. Issue 4 (August 2015) - Decker, Ann M.; Sheridan, Rachel; Lin, Guo-Hao; Sutthiboonyapan, Pimchanok; Carroll, William; Wang, Hom-Lay
Abstract : Introduction: Periimplant diseases have slowly become a common complication in implant patients. Here, we present a prognosis system to aid clinicians and researchers in the evaluation and treatment of periimplant diseases. This prognosis system divides periimplant disease into favorable, questionable, unfavorable, and hopeless cases based on the level of bone loss, pocket depth, mobility, bleeding on probing, and suppuration. Materials and Methods: To test the accuracy of our prognostic scale, the authors designed and conducted a database search to compile articles allowing for testing of the proposed prognostic scale. Discussion: The literature search returned 101 articles, of which two reported all relevant values for the prognostic system and were used to evaluate its reliability and accuracy. The prognostic system correctly predicted the likely outcome of periimplant disease up to 1 year posttreatment for all examined implants. Conclusions: The proposed prognostic system can be used as a tool for clinicians as they develop a treatment plan for all stages of periimplant disease.